Analisis Pergeseran Sektor Perekonomian Kabupaten Aceh Besar - Faisal Faisal (Syiah Kuala University, 2015)
This study aims to analyze the shift in the economic sector of Aceh Besar district and determine dominant sector. This study uses secondary data time series (time series) of the Gross Regional Domestic Product (GDP) of Aceh Besar and Aceh province in 2008-2010 and 2011-2013. The analytical tool used Klassen Tipology and Location Quotient (LQ). Based on the research results, Tipology Klassen analysis indicates that there has been a shift in the economic sector of Aceh Besar district where the agricultural sector as well as transport and communications sector earlier in the period 2008-2010 are in quadrant II (stagnant sector) in 2011-2013 has shifted to Quadrant IV (underdeveloped sector). Building and construction sector; hotel and restaurant trade and Services sector moved from quadrant I (developed sector) to quadrant II (stagnantsector). Location Quotient (LQ) shows a shift in the agriculture sector; Building and construction, trade, hotels and restaurants; Transport and communications; Finance, real estate and business services as well as services, from the basic sector into the non base. The economic sector that is still the basis of the sector in the economy of Aceh Besar regency are the building sector and construction. The local government of Aceh Besar district in order to keep attention to the development of the economic sectors as consideration for the economic development of the region to provide high impact for the improvement of people's income and employment.